2016
DOI: 10.1124/mol.116.104521
|View full text |Cite
|
Sign up to set email alerts
|

Protein RS1 (RSC1A1) Downregulates the Exocytotic Pathway of Glucose Transporter SGLT1 at Low Intracellular Glucose via Inhibition of Ornithine Decarboxylase

Abstract: Na-d-glucose cotransporter 1 (SGLT1) is rate-limiting for glucose absorption in the small intestine. Shortly after intake of glucose-rich food, SGLT1 abundance in the luminal membrane of the small intestine is increased. This upregulation occurs via glucose-induced acceleration of the release of SGLT1-containing vesicles from the trans-Golgi network (TGN), which is regulated by a domain of protein RS1 (RSC1A1) named RS1-Reg. Dependent on phosphorylation, RS1-Reg blocks release of vesicles containing SGLT1 or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…Similarly, in differentiated CaCo-2 cells, a model of human enterocytes, SGLT1, was localized to the BBM and intracellular vesicles [198]. The intracellular location of SGLT1/Sglt1 in enterocytes is consistent with data revealing a D-glucose-dependent regulation of the exocytotic pathway of SGLT1/Sglt1 in the small intestine of mouse and humans [66,341,408]. In rats, the BBM abundance and transport capacity of Sglt1 per unit length in the jejunum was higher compared to that in the duodenum and ileum [25,83,142,203].…”
Section: Transport Mode Selectivity and Location Of Glucose Transposupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, in differentiated CaCo-2 cells, a model of human enterocytes, SGLT1, was localized to the BBM and intracellular vesicles [198]. The intracellular location of SGLT1/Sglt1 in enterocytes is consistent with data revealing a D-glucose-dependent regulation of the exocytotic pathway of SGLT1/Sglt1 in the small intestine of mouse and humans [66,341,408]. In rats, the BBM abundance and transport capacity of Sglt1 per unit length in the jejunum was higher compared to that in the duodenum and ileum [25,83,142,203].…”
Section: Transport Mode Selectivity and Location Of Glucose Transposupporting
confidence: 84%
“…3). Accordingly, D-glucose-dependent upregulation of SGLT1 in the plasma membrane is due to a glucose-induced acceleration of the exocytotic pathway of SGLT1 from the Golgi that is modulated by protein RS1 (RSC1A1) [66,407,408]. Human SGLT1 or YFP-SGLT1 was expressed in oocytes, and the post-translational active domain of RS1 (RS1-Reg) or peptide motifs of RS1-Reg were injected into the oocytes.…”
Section: Short-term Post-translational Regulation In the Small Intestmentioning
confidence: 99%
“…RS1 regulates SGLT1 on transcriptional and post-translational levels. Post-translational regulation of SGLT1 was extensively investigated in vitro and was demonstrated in tissue of the small intestine (Veyhl et al 2006;Chintalapati et al 2016;Veyhl-Wichmann et al 2016), whereas transcriptional regulation was demonstrated in the renal cell line LLC-PK 1 (Korn et al 2001). In mice in which RS1 was removed (RS1 À/À mice), we observed that plasma membrane abundance of SGLT1 in small intestine was increased to a similar level as after glucose-induced post-translational up-regulation (Osswald et al 2005;Veyhl-Wichmann et al 2016).…”
mentioning
confidence: 77%
“…The finding that SGLT1 mRNA abundance after TBI was decreased in RS1 À/À mice was not expected because RS1 has been described to down-regulate SGLT1 expression. Previous data showed that RS1 which was localized in the cytosol, at the plasma membrane, at the Golgi, and within the nucleus (Kroiss et al 2006), down-regulates SGLT1 on the transcriptional and post-translational levels (Korn et al 2001;Veyhl et al 2006;Chintalapati et al 2016;Veyhl-Wichmann et al 2016). In LLC-PK 1 cells it has been shown that confluence-dependent migration of RS1 into the nucleus is steered by a nuclear location signal (Filatova et al 2009) and that removal of RS1 up-regulates SGLT1 transcription (Korn et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a mutation in MAP17 is also associated with familial renal glycosuria (see below), suggesting that MAP17 may be a physiological regulator of Sglt2 function (9). In a separate study, it was reported that RSC1A1 (RS1), a 67/68-kDa protein found in both the small intestine and all three segments of the kidney proximal tubule (24), serves as a regulator of Sglt1 (8,33,43,(57)(58)(59). RS1 localizes to the trans-Golgi network (TGN), plasma membrane, and nucleus in renal proximal tubule cells in culture (8,33,43,(57)(58)(59) Fig.…”
Section: Renal Glucose Handlingmentioning
confidence: 99%